Reasons for encounter and diagnoses of patients attending primary care clinics in the Saldanha Bay and Swartland rural sub districts, Western Cape Province : a prospective cross-sectional survey - Mathee, Shaheed (Stellenbosch : Stellenbosch University, 2010)
Thesis (MMed)--Stellenbosch University, 2012.